A kind of iron-silicon-chromium alloy soft magnetic powder core and preparation method thereof
Through a preparation method of ferrosilicon chromium alloy soft magnetic powder core, the problem that existing inductor components are difficult to improve magnetic permeability and mechanical strength when facing the precision of modern electronic devices is solved, and the effect of performance optimization and production process simplification is achieved.
Patent Information
- Application Number
- CN202510089487.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2045-01-21
AI Technical Summary
When facing the precision demand of modern electronic devices, existing inductive components are difficult to improve some attribute performance while maintaining their original attributes, especially in terms of magnetic permeability and mechanical strength.
A preparation method for ferrosilicon chromium alloy soft magnetic powder core is adopted to ensure the uniformity and performance optimization of the material by screening preset particle size of ferrosilicon chromium alloy powder, powder passivation, insulation coating, baking treatment, molding and curing treatment.
Under the premise of combining magnetic permeability and high toughness, through special baking treatment, the parameter values of IR and longitudinal extrusion strength can be effectively adjusted, meet the diverse needs of different customers, simplify the production process, and reduce production costs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of metal soft magnetic powder cores, and in particular to an iron-silicon-chromium alloy soft magnetic powder core and a preparation method thereof. Background Art
[0002] The one-piece molded inductor is a new type of inductor component that is formed by implanting a hollow coil into a mold and filling it with insulating powder. It has a full-enclosed structure, no magnetic leakage, and no mutual interference between devices. The product has the characteristics of small size, low loss, and excellent shielding performance. It is widely used in 5G communications, computers, consumer electronics, digital electronics, automotive electronics, artificial intelligence, industrial control, aerospace and other fields. With the continuous advancement of science and technology, various electronic devices produced and prepared in modern society are becoming more and more sophisticated, which is a new challenge for traditional inductor components. Only by continuously optimizing performance characteristics can we meet increasingly stringent requirements. Therefore, how to improve the performance of some attributes while ensuring that the original attributes are not overly affected has become the focus of current discussion. Summary of the invention
[0003] In view of the shortcomings of the prior art, the present application provides an iron-silicon-chromium alloy soft magnetic powder core and a preparation method thereof. The preparation method of the present application is simple, the reaction conditions are mild, the cost is low, and large-scale production can be automated. The iron-silicon-chromium alloy soft magnetic powder core prepared by the present application, while having both magnetic permeability and high toughness, can effectively adjust the parameter values of IR and longitudinal extrusion strength through special baking treatment, meet the different functional requirements of different customers, simplify the production process, and help enterprises reduce costs and increase efficiency.
[0004] In a first aspect, the present application provides a method for preparing an iron-silicon-chromium alloy soft magnetic powder core, using the following technical solution:
[0005] A method for preparing an iron-silicon-chromium alloy soft magnetic powder core comprises the following steps:
[0006] S1. Screening iron-silicon-chromium alloy powder of a preset particle size and weighing it according to a preset mass;
[0007] S2, powder passivation: weigh the required weight of the passivator, dissolve the passivator in an organic solvent to obtain a passivation solution, mix the passivation solution with the iron-silicon-chromium alloy powder, stir well, remove the organic solvent by standing and volatilizing naturally, and dry to obtain a passivation powder;
[0008] S3, insulation coating: after the organic solvent and the adhesive are evenly mixed, the passivation powder is added thereto, the mixture is stirred and mixed until it is semi-wetted, and granulated to obtain granulated powder;
[0009] S4, baking treatment: the granulated powder is left to stand for 8-12 hours to naturally volatilize and remove acetone, and then baked, and then cooled to room temperature and sieved again to obtain dry granulated powder with a particle size of 40-200 mesh;
[0010] S5, compression molding: adding lubricant to the dry granulated powder and stirring evenly, compression molding, cleaning the edges and corners burrs, and obtaining a blank;
[0011] S6. Curing treatment: curing the blank in an air atmosphere, and naturally cooling it to room temperature to obtain a cured blank.
[0012] By adopting the above technical scheme, in the preparation process of Fe-Si-Cr alloy soft magnetic powder core, each step plays a vital role, and they cooperate with each other to ensure the performance and quality of the final product. S1: Screening Fe-Si-Cr alloy powder with a preset particle size and weighing it according to the preset mass. Selecting powder with a suitable particle size is the basis for ensuring the uniformity and consistency of the material. By controlling the particle size distribution of the powder, the density and magnetic properties of the final product can be optimized. Provide a uniform base material for subsequent powder processing steps (such as passivation and insulation coating) to ensure the consistency and controllability of each step. S2: Powder passivation. Through passivation treatment, a protective film can be formed on the surface of Fe-Si-Cr alloy powder to prevent the powder from oxidizing during subsequent processing and improve the oxidation resistance and stability of the powder. The passivation treatment not only protects the powder, but also provides a clean and stable surface for the insulation coating step, which helps to improve the adhesion and uniformity of the insulation layer. S3: Insulation coating. Coating an insulating layer on the surface of the passivated powder can prevent direct contact between particles, reduce eddy current loss, and improve the magnetic properties and mechanical strength of the material. Insulation coating and passivation treatment complement each other to ensure that the powder maintains good insulation and mechanical strength during the granulation process, providing support for subsequent baking and compression molding. S4: Baking treatment Through baking treatment, the residual solvent in the granulated powder is removed and the granulated powder is completely dried. At the same time, the physical properties of the granulated powder, such as IR and longitudinal extrusion strength, are adjusted through appropriate temperature and time control. Baking treatment not only removes residual solvents, but also further optimizes the performance of granulated powder through temperature control, providing uniform and dry raw materials for compression molding. S5: Compression molding The dry granulated powder is molded into the required shape and size through compression molding, and lubricants are added to reduce friction and improve molding efficiency and yield. Compression molding is to make the material into the final shape based on the previous steps. The addition of lubricants ensures the smooth progress of the molding process, reduces the generation of burrs, and improves the appearance quality and consistency of the product. S6: Curing treatment, through curing treatment in air atmosphere, the mechanical strength and magnetic properties of the blank are further improved. At the same time, through natural cooling, the internal stress of the product is released and the dimensional stability is improved. Curing is the last step of the entire preparation process. It not only improves the mechanical strength of the product, but also optimizes the magnetic properties through temperature control, ensuring that the final product meets the performance requirements of customers. In summary, through precise control and coordination between each step, from the selection of raw materials to the curing of the final product, each step provides a guarantee for the high performance and consistency of the final product. This preparation method is not only simple and low-cost, but also suitable for large-scale automated production and can meet the functional requirements of different customers.
[0013] Preferably, in step S1, the iron-silicon-chromium alloy powder is prepared by a water-gas combined atomization method, and comprises, by mass percentage, Si 4.5-6.0wt%, Cr 4.0-6.0wt%, Mn 0.01-0.03wt%, and the remainder is Fe; the particle size of the iron-silicon-chromium alloy powder is 40-200 mesh.
[0014] Preferably, in step S2, the passivating agent is at least one of phosphoric acid, aluminum dihydrogen phosphate, phytic acid and oleic acid; and the organic solvent is at least one of ethyl acetate, butyl acetate, acetone and anhydrous ethanol.
[0015] Preferably, in step S2, the amount of the organic solvent is 6-15wt% of the mass of the Fe-Si-Cr alloy powder, and the amount of the passivator is 0.1-1.0wt% of the mass of the Fe-Si-Cr alloy powder; the mixing and stirring is specifically, stirring evenly for 10-15min at a constant temperature of 35°C with a magnetic stirrer at a speed of 300r / min to ensure that the passivator fully reacts with the surface of the Fe-Si-Cr alloy powder to form a passivation layer; the drying temperature is 60-100°C and the time is 40-60min.
[0016] Preferably, in step S3, the organic solvent is at least one of ethyl acetate, acetic acid, acetone and ethanol; the adhesive is at least one of sodium silicate, potassium silicate, modified silicone resin, polyvinyl butyral, and biphenyl phenol type self-flame retardant epoxy resin; the amount of the adhesive is 1.0-1.5% of the mass of the passivation powder, and the amount of the organic solvent is 8-15% of the mass of the passivation powder.
[0017] Preferably, the adhesive is composed of potassium silicate and biphenyl phenol type self-flame retardant epoxy resin in a mass ratio of 5:2.
[0018] By adopting the above technical solution, potassium silicate, as an inorganic adhesive, can form a stable connection between the powder core particles and improve the mechanical strength and hardness of the powder core. Potassium silicate has good thermal stability and chemical stability, which helps to maintain the dimensional stability of the powder core during high-temperature baking and prevent the powder core from deforming due to temperature changes. Potassium silicate can reduce the hygroscopicity of the powder core, thereby improving the performance stability of the powder core in a humid environment. Biphenyl phenol type self-flame retardant epoxy resin has excellent heat resistance, can maintain good physical and chemical properties at high temperatures, and is suitable for high-temperature baking treatment. The resin itself has flame retardant properties, which can improve the safety performance of the powder core to a certain extent and prevent fires during production and use. Biphenyl phenol type self-flame retardant epoxy resin has good adhesion and high toughness, which can enhance the bonding force between the particles inside the powder core and improve the overall strength and impact resistance of the powder core. The resin has a low dielectric constant, which helps to improve the electrical properties of the powder core and reduce losses. The synergistic effect of potassium silicate and biphenyl phenol type self-flame retardant epoxy resin can improve the toughness and dimensional stability of the powder core while maintaining high strength and hardness, so that the powder core exhibits excellent comprehensive performance under various working conditions. The thermal stability and chemical stability of potassium silicate combined with the heat resistance of biphenyl phenol type self-flame retardant epoxy resin enables the powder core to maintain good dimensional stability and chemical stability during high-temperature baking, preventing deformation and performance degradation. The low hygroscopicity of potassium silicate complements the flame retardant properties and low dielectric constant of biphenyl phenol type self-flame retardant epoxy resin, further improving the performance stability of the powder core in humid environments and electrical applications. In summary, the synergistic effect of potassium silicate and biphenyl phenol type self-flame retardant epoxy resin in the preparation of iron-silicon-chromium alloy soft magnetic powder core improves the comprehensive performance of the powder core.
[0019] Preferably, in step S4, the process conditions of the baking treatment are: baking temperature is 50° C.-110° C., and baking time is 60 min-150 min.
[0020] By adopting the above technical scheme, the baking treatment can completely remove the residual organic solvents in the granulation powder, such as acetone, to ensure the purity and stability of the material. By controlling the baking temperature and time, the internal stress distribution of the iron-silicon-chromium alloy soft magnetic powder core can be effectively adjusted, thereby improving its magnetic permeability and toughness. At the same time, the baking treatment can also reduce the internal stress of the material, prevent cracking and deformation, and enhance the mechanical strength of the finished product. The baking treatment can be carried out under mild conditions, without the need for complex equipment and harsh environment, and is suitable for large-scale automated production, which helps to reduce production costs. Adhesives (such as potassium silicate, biphenyl phenol type self-flame retardant epoxy resin, etc.) will undergo cross-linking reactions to form a stable network structure, further enhancing the dimensional stability and chemical stability of the material. The heat resistance and low hygroscopicity of biphenyl phenol type self-flame retardant epoxy resin also help to improve the performance of the material in high temperature and humid environments. The baking treatment can promote the passivation agent to form a dense protective layer on the surface of the material, prevent oxidation and corrosion, and extend the service life of the material. The baking treatment can make the insulating coating more uniform and firm, improve the electrical insulation performance of the material, reduce eddy current losses, and enhance the overall magnetic properties. In summary, baking treatment plays a key role in the preparation process of Fe-Si-Cr alloy soft magnetic powder core. It not only improves the comprehensive performance of the material, but also simplifies the production process and reduces the production cost. It is an important process step to achieve high-performance soft magnetic powder core.
[0021] Preferably, in step S5, the lubricant is at least one of paraffin powder, hexagonal boron nitride, microcrystalline wax and zinc stearate; the amount of the lubricant is 0.1-0.9wt% of the mass of the granulated powder, and the pressure of the compression molding is 8-19T / cm 2 .
[0022] Preferably, in step S6, the process conditions of the curing treatment are: gradually increase the temperature in the following stages: in the first stage, the temperature is increased to 60°C at a constant speed over 30 minutes at room temperature, and kept warm for 30 minutes in the second stage; in the third stage, the temperature is increased to 90°C at a constant speed over 30 minutes and kept warm for 30 minutes; in the fourth stage, the temperature is increased to 120°C at a constant speed over 30 minutes and kept warm for 45 minutes; in the fifth stage, the temperature is increased to 180°C at a constant speed over 45 minutes and kept warm for 120 minutes, and then naturally cooled to room temperature.
[0023] In a second aspect, the present application provides an iron-silicon-chromium alloy soft magnetic powder core, which adopts the following technical solution:
[0024] As a general technical concept, the present application also provides an iron-silicon-chromium alloy soft magnetic powder core prepared by the above-mentioned method for preparing the iron-silicon-chromium alloy soft magnetic powder core.
[0025] In summary, the present application includes at least one of the following beneficial technical effects:
[0026] 1. Simple preparation process: The reaction conditions of the entire preparation process are mild, the operation is simple, and it is easy to realize automated large-scale production, which reduces production costs and improves production efficiency.
[0027] 2. Cost control: Due to the simple preparation method and mild reaction conditions, the overall production cost can be effectively controlled, which is conducive to the company's advantage in market competition.
[0028] 3. Excellent magnetic properties: The prepared iron-silicon-chromium alloy soft magnetic powder core not only has high magnetic permeability, but also has high toughness, which can improve the mechanical strength and durability of the product while maintaining good magnetic properties.
[0029] 4. Flexible parameter adjustment: Through special baking treatment, the IR and longitudinal extrusion strength of the Fe-Si-Cr alloy soft magnetic powder core can be effectively adjusted to meet the diverse needs of different customers and enhance the market adaptability of the product.
[0030] 5. Strong dimensional and chemical stability: Biphenyl phenol type self-flame retardant epoxy resin is used as the adhesive. Its excellent heat resistance, low moisture absorption, self-flame retardant properties and high toughness work synergistically with potassium silicate to significantly improve the dimensional stability and chemical stability of the iron-silicon-chromium alloy soft magnetic powder core and extend the service life of the product.
[0031] 6. Good environmental performance: The organic solvents and adhesives used are environmentally friendly materials, which reduce environmental pollution during the production process and conform to the concept of modern green manufacturing. DETAILED DESCRIPTION
[0032] The embodiments of the present application will be described in detail below in conjunction with the examples, but those skilled in the art will understand that the following examples are only used to illustrate the present application and should not be considered to limit the scope of the present application. If the specific conditions are not specified in the examples, they are carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially. The biphenyl phenol type self-flame retardant epoxy resin was purchased from Hunan Jiashengde Materials Technology Co., Ltd., brand: BPNE3501, and the modified silicone resin was purchased from Hubei Longsheng Sihai New Materials Co., Ltd.
[0033] In the following embodiments, the iron-silicon-chromium alloy powder used is prepared by a water-gas combined atomization method, and comprises, by mass percentage, 4.6wt% Si, 5.3wt% Cr, 0.02wt% Mn, and the remainder Fe, and its particle size is 40-200 mesh. Example 1
[0034] A method for preparing an iron-silicon-chromium alloy soft magnetic powder core comprises the following steps:
[0035] S1. Powder passivation: Take 6% of acetone and 0.1% of oleic acid, which account for 6% of the mass of the iron-silicon-chromium alloy powder, mix them, then slowly add the iron-silicon-chromium alloy powder into them, stir them evenly at a constant temperature of 35°C with a magnetic stirrer at a speed of 300r / min for 10 minutes, remove the acetone by natural volatilization by standing, and then transfer them to an oven for drying at a baking temperature of 60°C and a baking time of 60 minutes to obtain a passivated powder;
[0036] S2, insulation coating: take 6% of the mass of passivation powder and 1% of adhesive, mix, then slowly add the passivation powder, stir and mix until semi-wet state, sieve through 40-200 mesh sieve, take powder with particle size between 40-200 mesh, granulate to obtain granulated powder; the adhesive is sodium silicate;
[0037] S3, baking treatment: the granulated powder is left to stand for 8 hours to naturally volatilize and remove acetone, and then baked at a temperature of 110° C. for 60 minutes, and then cooled to room temperature and sieved again to obtain dry granulated powder with a particle size of 40-200 mesh;
[0038] S4. Compression molding: Add 0.1% zinc stearate by weight to the dry granulated powder, stir evenly, take 4g and mold it at room temperature with a molding pressure of 8T / cm 2 , clean the burrs on the edges and corners to obtain the blank;
[0039] S5. Curing treatment: The blank is cured in an air atmosphere, and the process conditions of the curing treatment are: gradually increase the temperature in the following stages: in the first stage, the temperature is increased to 60°C at an average speed of 30 minutes at room temperature, and the temperature is kept for 30 minutes in the second stage; in the third stage, the temperature is increased to 90°C at an average speed of 30 minutes and kept for 30 minutes; in the fourth stage, the temperature is increased to 120°C at an average speed of 30 minutes and kept for 45 minutes; in the fifth stage, the temperature is increased to 180°C at an average speed of 45 minutes and kept for 120 minutes, and then naturally cooled to room temperature to obtain a cured blank. Example 2
[0040] A method for preparing an iron-silicon-chromium alloy soft magnetic powder core comprises the following steps:
[0041] S1. Powder passivation: 15% of acetone and 1.0% of aluminum dihydrogen phosphate accounting for the mass of the iron-silicon-chromium alloy powder are mixed, and then the iron-silicon-chromium alloy powder is slowly added thereto, and stirred evenly for 15 minutes with a magnetic stirrer at a speed of 300 r / min in a constant temperature environment of 35°C, and the acetone is removed by natural volatilization by standing, and then transferred to an oven for drying at a baking temperature of 100°C and a baking time of 40 minutes to obtain a passivated powder;
[0042] S2, insulation coating: take 15% of acetone and 1.5% of adhesive accounting for the mass of passivation powder, mix, then slowly add passivation powder thereto, stir and mix until semi-wetted, sieve through a 40-200 mesh sieve, take powder with a particle size between 40-200 mesh, granulate to obtain granulated powder; the adhesive is biphenyl phenol type self-flame retardant epoxy resin;
[0043] S3, baking treatment: the granulated powder is left to stand for 12 hours to naturally volatilize and remove acetone, and then baked at a temperature of 80° C. for 150 minutes, and then cooled to room temperature and sieved again to obtain dry granulated powder with a particle size of 40-200 mesh;
[0044] S4, compression molding: Add 0.9% paraffin powder by weight to the dry granulated powder, stir evenly, take 4g and mold it at room temperature with a molding pressure of 19T / cm 2 , clean the burrs on the edges and corners to obtain the blank;
[0045] S5. Curing treatment: The blank is cured in an air atmosphere, and the process conditions of the curing treatment are: gradually increase the temperature in the following stages: in the first stage, the temperature is increased to 60°C at an average speed of 30 minutes at room temperature, and the temperature is kept for 30 minutes in the second stage; in the third stage, the temperature is increased to 90°C at an average speed of 30 minutes and kept for 30 minutes; in the fourth stage, the temperature is increased to 120°C at an average speed of 30 minutes and kept for 45 minutes; in the fifth stage, the temperature is increased to 180°C at an average speed of 45 minutes and kept for 120 minutes, and then naturally cooled to room temperature to obtain a cured blank. Example 3
[0046] A method for preparing an iron-silicon-chromium alloy soft magnetic powder core comprises the following steps:
[0047] S1. Powder passivation: 11% of acetone and 0.5% of phytic acid accounting for the mass of the iron-silicon-chromium alloy powder are mixed, and then the iron-silicon-chromium alloy powder is slowly added thereto, and stirred evenly for 12 minutes with a magnetic stirrer at a speed of 300 r / min in a constant temperature environment of 35°C, and the acetone is removed by natural volatilization by standing, and then transferred to an oven for drying at a baking temperature of 80°C and a baking time of 50 minutes to obtain a passivated powder;
[0048] S2, insulation coating: take 9% of acetone and 1.2% of adhesive by weight of the passivation powder, mix them, then slowly add the passivation powder thereto, stir and mix until semi-wetted, sieve through a 40-200 mesh sieve, take powder with a particle size between 40-200 mesh, granulate to obtain granulated powder; the adhesive is polyvinyl butyral;
[0049] S3, baking treatment: the granulated powder is left to stand for 10 hours to naturally volatilize and remove acetone, and then baked at a temperature of 50° C. for 120 minutes, and then cooled to room temperature and sieved again to obtain dry granulated powder with a particle size of 40-200 mesh;
[0050] S4. Compression molding: Add 0.5% hexagonal boron nitride by weight to the dry granulated powder, stir evenly, take 4g and mold it at room temperature with a molding pressure of 13T / cm 2 , clean the burrs on the edges and corners to obtain the blank;
[0051] S5. Curing treatment: The blank is cured in an air atmosphere, and the process conditions of the curing treatment are: gradually increase the temperature in the following stages: in the first stage, the temperature is increased to 60°C at an average speed of 30 minutes at room temperature, and the temperature is kept for 30 minutes in the second stage; in the third stage, the temperature is increased to 90°C at an average speed of 30 minutes and kept for 30 minutes; in the fourth stage, the temperature is increased to 120°C at an average speed of 30 minutes and kept for 45 minutes; in the fifth stage, the temperature is increased to 180°C at an average speed of 45 minutes and kept for 120 minutes, and then naturally cooled to room temperature to obtain a cured blank. Example 4
[0052] The same as Example 3, except that in step S3, the baking temperature is 80°C. Example 5
[0053] The same as Example 3, except that in step S3, the baking temperature is 110°C. Example 6
[0054] The same as Example 3, except that in step S2, the adhesive is potassium silicate. Example 7
[0055] The same as Example 6, except that in step S3, the baking temperature is 80°C. Example 8
[0056] The same as Example 6, except that in step S3, the baking temperature is 110°C. Example 9
[0057] The same as Example 3, except that in step S2, the adhesive is sodium silicate. Example 10
[0058] The same as Example 9, except that in step S3, the baking temperature is 80°C. Embodiment 11
[0059] The same as Example 9, except that in step S3, the baking temperature is 110°C. Example 12
[0060] The same as Example 3, except that in step S2, the adhesive is a modified silicone resin. Embodiment 13
[0061] The same as Example 12, except that in step S3, the baking temperature is 80°C. Embodiment 14
[0062] The same as Example 12, except that in step S3, the baking temperature is 110°C. Embodiment 15
[0063] The same as Example 3, except that in step S2, the adhesive is a biphenyl phenol type self-flame retardant epoxy resin. Example 16
[0064] The same as Example 15, except that in step S3, the baking temperature is 80°C. Embodiment 17
[0065] The same as Example 15, except that in step S3, the baking temperature is 110°C. Embodiment 18
[0066] The method is the same as Example 3, except that in step S2, the adhesive is composed of potassium silicate and biphenyl phenol type self-flame retardant epoxy resin in a mass ratio of 5:2. Embodiment 19
[0067] The same as Example 18, except that in step S3, the baking temperature is 80°C. Embodiment 20
[0068] The same as Example 18, except that in step S3, the baking temperature is 110°C.
[0069] The iron-silicon-chromium alloy soft magnetic powder core prepared in the above-mentioned embodiments is a magnetic ring with an outer diameter of 14 mm and an inner diameter of 8 mm.
[0070] Performance Testing
[0071] The magnetic rings prepared in Examples 3 to 20 were sampled respectively. The magnetic rings were made of 0.65 mm enameled wire and wound with 14 turns. Inductance tests were performed in accordance with standard SJ20966-2006. MATS-2010SA soft magnetic material dynamic measuring device (LCR meter for short) was used to measure magnetic performance parameters such as magnetic permeability and insulation resistance of the magnetic rings. The μ value is μe=(L*Le*10000) / (4*3.1415*Ae*N2), μe: effective magnetic permeability, L: inductance (μH), Le: effective magnetic path length (mm), Ae: effective cross-sectional area (mm 2 ), N: number of coil turns; RS is directly tested by MICROTEST 6377 (LCR meter); IR is directly tested by a withstand voltage tester; height is measured by a vernier caliper; longitudinal extrusion strength is tested in accordance with GB / T3656-2008; the test results are shown in Table 1.
[0072] Table 1 Performance test of each embodiment
[0073]
[0074] Analyzing the data in Table 1, we can see that:
[0075] 1) The soft magnetic powder core of the iron-silicon-chromium alloy prepared in Examples 3 to 20, while having both magnetic permeability and high toughness, can effectively adjust the parameter values of IR and longitudinal extrusion strength only through baking treatment at a specific temperature, thereby meeting the different functional requirements of different customers, simplifying the production process, and helping enterprises to reduce costs and increase efficiency.
[0076] 2) Under the premise of controlling the same raw materials, preparation process flow, process parameters, etc. to be exactly the same, adjusting different baking temperatures will lead to certain differences in the parameter specifications of the final product, among which the change rules of IR and longitudinal extrusion strength are more obvious, and other parameters are also significantly different under low and high temperature conditions; therefore, according to customer requirements for product performance, it is only necessary to make different adjustments to the baking treatment in the preparation method of this application, and adopt other identical steps and processes to obtain products with different performances, so as to meet different customer needs, simplify the production process, and help enterprises reduce costs and increase efficiency.
[0077] 3) The comparative analysis of the performance of the iron-silicon-chromium alloy soft magnetic powder cores prepared by Examples 18 to 20 and the corresponding Examples 15 to 17 and Examples 6 to 8 shows that the adhesive is composed of potassium silicate and biphenylphenol type self-flame retardant epoxy resin in a mass ratio of 5:2. The synergistic effect between them can not only enhance the comprehensive performance of the iron-silicon-chromium alloy soft magnetic powder core, but also ensure its reliability and stability in practical applications.
[0078] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation methods of the present application can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing an iron-silicon-chromium alloy soft magnetic powder core, characterized in that: The following steps are involved: S1. Screening iron-silicon-chromium alloy powder of a preset particle size and weighing it according to a preset mass; S2, powder passivation: weigh the required weight of the passivator, dissolve the passivator in an organic solvent to obtain a passivation solution, mix the passivation solution with the iron-silicon-chromium alloy powder, stir well, remove the organic solvent by standing and volatilizing naturally, and dry to obtain a passivation powder; S3, insulation coating: after the organic solvent and the adhesive are evenly mixed, the passivation powder is added thereto, the mixture is stirred and mixed until it is semi-wetted, and granulated to obtain granulated powder; the organic solvent is at least one of ethyl acetate, acetic acid, acetone and ethanol; the adhesive is composed of potassium silicate and biphenyl phenol type self-flame retardant epoxy resin in a mass ratio of 5:2; the amount of the adhesive is 1.0-1.5% of the mass of the passivation powder, and the amount of the organic solvent is 8-15% of the mass of the passivation powder; S4, baking treatment: the granulated powder is allowed to stand for 8-12 hours to naturally volatilize and remove acetone, and then baked, and then cooled to room temperature, and sieved again to obtain dry granulated powder with a particle size of 40-200 mesh; wherein the process conditions of the baking treatment are: baking temperature of 80°C-110°C, and baking time of 120min-150min; S5, compression molding: adding lubricant to the dry granulated powder and stirring evenly, compression molding, cleaning the edges and corners burrs, and obtaining a blank; S6. Curing treatment: curing the blank in an air atmosphere, naturally cooling it to room temperature to obtain a cured blank; the process conditions of the curing treatment are: gradually increasing the temperature in the following stages: in the first stage, the temperature is increased to 60°C at a constant speed over 30 minutes, and the second stage is kept warm for 30 minutes; in the third stage, the temperature is increased to 90°C at a constant speed over 30 minutes, and kept warm for 30 minutes; in the fourth stage, the temperature is increased to 120°C at a constant speed over 30 minutes, and kept warm for 45 minutes; in the fifth stage, the temperature is increased to 180°C at a constant speed over 45 minutes, and kept warm for 120 minutes, and then naturally cooled to room temperature.
2. The method for preparing an Fe-Si-Cr alloy soft magnetic powder core according to claim 1, characterized in that: In step S1, the iron-silicon-chromium alloy powder is prepared by a water-gas combined atomization method, and comprises, by mass percentage, Si 4.5-6.0wt%, Cr 4.0-6.0wt%, Mn 0.01-0.03wt%, and the remainder is Fe; the particle size of the iron-silicon-chromium alloy powder is 40-200 meshes.
3. The method for preparing an Fe-Si-Cr alloy soft magnetic powder core according to claim 1, characterized in that: In step S2, the passivating agent is at least one of phosphoric acid, aluminum dihydrogen phosphate, phytic acid and oleic acid; and the organic solvent is at least one of ethyl acetate, butyl acetate, acetone and anhydrous ethanol.
4. The method for preparing an Fe-Si-Cr alloy soft magnetic powder core according to claim 1, characterized in that: In step S2, the amount of the organic solvent is 6-15wt% of the mass of the Fe-Si-Cr alloy powder, and the amount of the passivator is 0.1-1.0wt% of the mass of the Fe-Si-Cr alloy powder; the mixing and stirring is specifically, stirring evenly for 10-15min at a constant temperature of 35°C with a magnetic stirrer at a speed of 300r / min to ensure that the passivator fully reacts with the surface of the Fe-Si-Cr alloy powder to generate a passivation layer; the drying temperature is 60-100°C and the time is 40-60min.
5. The method for preparing an Fe-Si-Cr alloy soft magnetic powder core according to claim 1, characterized in that: In step S5, the lubricant is at least one of paraffin powder, hexagonal boron nitride, microcrystalline wax and zinc stearate; the amount of the lubricant is 0.1-0.9wt% of the mass of the granulated powder, and the pressure of the compression molding is 8-19T / cm 2 .
6. An iron-silicon-chromium alloy soft magnetic powder core, characterized in that: The iron-silicon-chromium alloy soft magnetic powder core is prepared by the preparation method of the iron-silicon-chromium alloy soft magnetic powder core according to any one of claims 1-5.
Citation Information
Patent Citations
Iron-silicon-chromium soft magnetic powder material
CN114156037A
High-frequency high-permeability metal soft magnetic powder core and preparation method thereof
CN119230282A